2006
DOI: 10.1017/s000842390606015x
|View full text |Cite
|
Sign up to set email alerts
|

Electoral Participation in Municipal, Provincial and Federal Elections in Canada

Abstract: Abstract.The purpose of this paper is to highlight the importance of social relations or social capital for voting turnout at three levels of Canadian government, paying particular attention to social contexts, socio-demographics and socio-economic forces. The data source is the Public Use Microdata File from theNational Survey of Giving, Volunteering and Participation, administered by Statistics Canada (2001). Results provide support for social capital theory. Those who donate to charities and/or volunteer ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
6

Year Published

2008
2008
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 57 publications
0
21
0
6
Order By: Relevance
“…Quant à l'influence de l’âge sur le comportement électoral à l’échelle municipale, ce constat dans le cas du Québec est semblable à celui élaboré à l’échelle provinciale (Gélineau et Morin-Chassé, 2009) selon lequel les électeurs âgés votent davantage que les électeurs plus jeunes. Nakhaie (2006) a d'ailleurs trouvé un résultat semblable sur des données individuelles en comparant la participation aux différents paliers de gouvernement. Ces résultats mettent toutefois à l'avant-plan l'importance du cycle de vie sur le comportement électoral, élément absent des études actuelles sur le comportement politique à l’échelle municipale.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Quant à l'influence de l’âge sur le comportement électoral à l’échelle municipale, ce constat dans le cas du Québec est semblable à celui élaboré à l’échelle provinciale (Gélineau et Morin-Chassé, 2009) selon lequel les électeurs âgés votent davantage que les électeurs plus jeunes. Nakhaie (2006) a d'ailleurs trouvé un résultat semblable sur des données individuelles en comparant la participation aux différents paliers de gouvernement. Ces résultats mettent toutefois à l'avant-plan l'importance du cycle de vie sur le comportement électoral, élément absent des études actuelles sur le comportement politique à l’échelle municipale.…”
Section: Discussionunclassified
“…Pour certains, une telle idée néglige de nombreux aspects et la taille de la municipalité ne permet pas à elle seule d'expliquer la participation électorale (Kelleher et Lowery, 2004). Caren (2007) Nakhaie (2006) montre que c'est surtout l'âge de celui-ci qui aurait un impact important sur la participation électorale à l'échelle municipale au Canada, et ce de façon encore plus prépondérante qu'aux autres niveaux de gouvernement.…”
Section: L'effet Du Contexte Sociospatial Et Sociodémographiqueunclassified
“…Oliver and colleagues (2012) for example, identified the local voter profile as being white, elderly, homeowning, educated and with above-average income. In Canada, Nakhaie (2006) showed that age is the primary explanatory variable of behaviour in municipal elections. Trounstine, however, reminds us that although the sociodemographic context should not be neglected in the analysis of local electoral participation, the political context remains important and it should therefore be analyzed in detail (2009: 613).…”
Section: Influences On Voter Turnoutmentioning
confidence: 99%
“…Through these skills and abilities, immigrants can acquire information and understand the mechanisms related to political participation. Immigrants' higher educational attainment tends to increase while their lower language ability decreases their political knowledge and participa-tion~Pattie and Johnston, 2003;Gidengil et al, 2004;Bloemraad, 2006;Nakhaie, 2006!. Nevertheless, studies that do take into account socioeconomic differences between immigrants and those born in Canada still show differential political participation between these groups~see Black, 1991;White et al, 2006;Reitz and Banerjee, 2007;Howe, 2007!. Another explanation for differential participation of immigrants and those born in Canada might be due to the differences in social relations, norms and values between these groups.…”
Section: Immigrants and Political Participationmentioning
confidence: 99%
“…Others have taken Putnam's lead and evaluated the importance of social capital in the domain of politics. They have shown that membership in voluntary participation stimulates political participa-tion~Wolfinger and Rosenstone, 1980;Verba et al, 1995;Tossutti, 2003!. Those who are active in voluntary associations pay more attention to news about politics in media, have more interest in politics and engage in more political discussion than their counterparts~see Gidengil et al, 2004!. Nonvoters are more likely to be socially isolated, and are less likely to volunteer or belong to organizations and associations~Sabucedo and Cramer, 1991; Ragsdale and Rusk, 1993;Pattie and Johnston, 1998;Nakhaie, 2006!. Similarly, the relationship between marital status, residential mobility, home ownership, social networks and community residence with voter turnout all point to the role of social capital for political participation~Eagles and Erfle, 1989;Pattie and Johnston, 1998;Tossutti, 2003;Nakhaie, 2006!.…”
Section: Social Capital and Political Participationmentioning
confidence: 99%